Metabolic Stability Assessment of Larotrectinib Using Liquid Chromatography Tandem Mass Spectrometry - Attwa MW; Kadi AA; Darwish HW (Drug Design, Development and Therapy, 2020)
Mohamed W Attwa, 1, 2 Adnan A Kadi, 1 Hany W Darwish 1, 3 1Department of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, Riyadh 11451, Saudi Arabia; 2Students’ University Hospital, Mansoura University, Mansoura 35516, Egypt; 3Analytical Chemistry Department, Faculty of Pharmacy, Cairo University, Cairo 11562, EgyptCorrespondence: Hany W Darwish Tel +966 1146 77343Fax +966 1146 76 220Email hdarwish@ksu.edu.saIntroduction: Larotrectinib (VITRAKVI) is an orally potent tropomyosin receptor kinase (Trk) inhibitor that acts by competitive inhibition of all corresponding receptor kinases. It demonstrated a marked response rate (75%) and robust anticancer activity in Trk fusion-positive patients. This response is independent of cancer type, age and gender.Methods: In this study, an efficient and accurate LC-MS/MS analytical method was developed for Larotrectinib (LRB) quantification in addition to evaluation of its metabolic stability. LRB and lapatinib (LTP) (which is chosen as an internal standard; IS) were eluted utilizing an isocratic mobile phase with a reversed phase elution system (C 18 column).Results and Discussion: The linearity range of the established method was 5– 500 ng/mL (r 2 ≥ 0.9999) in the human liver microsomes (HLMs) matrix. Various parameters were calculated to validate the method sensitivity (limit of quantification was 5 ng/mL) and reproducibility (inter and intra-day accuracy and precision were below 3% in all samples) of our methodology. For evaluation of LRB metabolic stability in HLMs matrix, in vitro half-life (48.8 min) and intrinsic clearance (14.19 μL/min/mg) were computed.Conclusion: Accordingly, we can conclude that LRB is a moderate extraction ratio drug when compared with other tyrosine kinase inhibitors (TKIs). According to our knowledge, the discussed procedure in this study is the first LC-MS/MS analytical method for evaluating LRB metabolic stability.Keywords: larotrectinib, human liver microsomes, metabolic stability evaluation, tandem mass spectrometry